The Effect of Layer Leaves on Reducing Uric Acid in the Elderly: A Systematic Review - Nurhayati, Isnani; Hidayat, Anas Rahmad; Yuniarti, Tri; Widiyanto, Aris (GLOBAL HEALTH SCIENCE GROUP, 2024)
Gout is an inflammatory disease of the joints caused by excess uric acid content in the blood, resulting in a buildup of uric acid crystals in the joints and other soft tissues. Bay leaf or with the Latin name Syzygium Polyanthum is a plant that can be used to treat gout. This study aims to estimate the effect of bay leaves on reducing uric acid levels in the elderly. This research is a systematic review research using the PRISMA diagram. Article searches were carried out based on the PICO Model eligibility criteria. P= Elderly; I= Drink boiled bay leaves; C= Do not drink bay leaf decoction; O= Uric acid. The articles used come from 1 database, namely: Google Scholar. With keywords including